MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI POHON LITERASI PADA SISWA KELAS 3 DI SDN 2 TELAGA BIRU - Fadhilah Hajarwati Abas; Amna Limonu; Helmi Y Supu; Ni Ketut Sri Ariyanti; Abdul Rahmat; Isnanto Isnanto (Jurnal Sosial Humaniora dan Pendidikan, 2022)
MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI POHON LITERASI PADA SISWA KELAS 3 DI SDN 2 TELAGA BIRU Fadhilah Hajarwati Abasa, Amna Limonub, Helmi Y Supuc, Ni Ketut Sri Ariyantid, Abdul Rahmate, Isnantof aFakultas Ilmu Pendidikan, fadhilahabas01@gmail.com, Universitas Negeri Gorontalo bFakultas Ilmu Pendidikan, amnalimonu2002@gmail.com2,Helmisupu4@gmail.com, Universitas Negeri Gorontalo cFakultas Ilmu Pendidikan, witnansihrahmatyatanaiyo@gmail.com, Universitas Negeri Gorontalo dFakultas Ilmu Pendidikan, niketutsriariyanti@gmail.com, Universitas Negeri Gorontalo eFakultas Ilmu Pendidikan, abdulrahmat@ung.ac.id, Universitas Negeri Gorontalo fFakultas Ilmu Pendidikan, isnanto@ung.ac.id, Universitas Negeri Gorontalo ABSTRACT The literacy tree is one of the media used to increase student motivation, especially in grade 3 elementary school. In the literacy tree, there are several motivational words for student learning so that they can be read by 3rd grade students. This literacy tree not only increases students' learning motivation but also increases students' interest in reading and students' creativity. Reading the motivational words that we made together with Grade 3 students will motivate students to learn, their interest in reading will increase and their creativity will increase through making literacy trees. The main purpose of this literacy tree is to increase student learning motivation in grade 3 students at SDN 2 Telaga Biru.